2001
DOI: 10.1093/pcp/pce042
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an Isoform of Rice Starch Branching Enzyme, RBE4, in Developing Seeds

Abstract: cDNA clones encoding an isoform of starch branching enzyme, RBE4, have been identified from a developing rice seed cDNA library, using a synthetic oligonucleotide probe corresponding to the N-terminal amino acid sequence of RBE4. The cDNA-derived amino acid sequence indicated that RBE4 is initially produced as a precursor protein of 841 amino acids, including a 53-residue transit peptide at the N-terminus. The mature form of RBE4 shared a high degree of sequence identity (80%) with mature RBE3, and possessed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 32 publications
4
41
0
Order By: Relevance
“…Thus, the lower activity of SBE under the high-nitrogen condition may be due to, at least in part, the decrease in the expression level of RBE4. In rice plants, although the expression level of RBE4 was similar to that of RBE1 in the leaves, RBE1 was expressed more intensively in seeds than in leaves and stems, while RBE4 was expressed in the leaves as well as in the developing seeds Mizuno et al, 2001). In Mutator insertional maize mutant of BEIIa type starch branching enzyme, to which RBE4 belongs, short chains of amylopectin were much diminished in leaf starch, but there was no difference in the chainprofi le for amylopectin of kernel starch between the mutant and wild-type (Blauth et al, 2001).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Thus, the lower activity of SBE under the high-nitrogen condition may be due to, at least in part, the decrease in the expression level of RBE4. In rice plants, although the expression level of RBE4 was similar to that of RBE1 in the leaves, RBE1 was expressed more intensively in seeds than in leaves and stems, while RBE4 was expressed in the leaves as well as in the developing seeds Mizuno et al, 2001). In Mutator insertional maize mutant of BEIIa type starch branching enzyme, to which RBE4 belongs, short chains of amylopectin were much diminished in leaf starch, but there was no difference in the chainprofi le for amylopectin of kernel starch between the mutant and wild-type (Blauth et al, 2001).…”
Section: Discussionmentioning
confidence: 91%
“…The gene expression level of RBE1 in the leaves was found to be very low (Mizuno et al, 1992;. The RBE4 was expressed in the leaves as well as in the developing seeds (Mizuno et al, 2001). Then, in this study, the transcripts level of RBE1 and RBE4 were analyzed in the second leaf sheath at growth stage 2 (fi rst leaf stage) by semi-quantitative RT-PCR.…”
Section: Expression Analysis Of Agps and Rbe Genes In The Second Leafmentioning
confidence: 91%
“…BEIIb is specifically or predominantly found in the endosperm, whereas BEIIa is present in almost all tissues of maize (Fisher et al, 1996;Gao et al, 1997), barley (Sun et al, 1998), and rice (Yamanouchi and Nakamura, 1992;Mizuno et al, 1993). Although there are some differences in terms of amino acid sequence between BEIIa and BEIIb, several investigators Takeda et al, 1993;Mizuno et al, 2001) reported that the substrate specificities of the two enzymes are indistinguishable. The critical decreases in the proportion of short chains with DP Ϲ 17 (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…In the developing wheat endosperm, the expression of SBEIIb is at a much lower level than SBEIIa [72,73], in contrast to the maize endosperm [74]. In rice, SBEIIa is at the earliest expressed 3 days after flowering (DAF) and maximally at 5-7 DAF, while SBEI and SBEIIb are most abundant at 7-10 DAF [75,76]. SBEII isoforms are partitioned between the plastid stroma and the starch granules [57], although the factors or mechanisms involved remain incompletely determined.…”
Section: Starch-branching Enzymes (Sbes)mentioning
confidence: 99%